2011
DOI: 10.1158/0008-5472.can-10-2719
|View full text |Cite
|
Sign up to set email alerts
|

Biological Roles of the Delta Family Notch Ligand Dll4 in Tumor and Endothelial Cells in Ovarian Cancer

Abstract: Emerging evidence suggests that the Notch/Delta-like ligand 4 (DLL4) pathway may offer important new targets for anti-angiogenesis approaches. In this study, we investigated the clinical and biological significance of DLL4 in ovarian cancer. DLL4 was overexpressed in 72% of tumors examined where it was an independent predictor of poor survival. Patients with tumors responding to anti-VEGF therapy had lower levels of DLL4 than patients with stable or progressive disease. Under hypoxic conditions, VEGF increased… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 27 publications
(35 reference statements)
7
79
0
Order By: Relevance
“…Notch is a key pathway in ovarian cancer, and Dll4 is overexpressed in up to 72% of ovarian carcinomas (15,29). Enoticumab had activity in patients with ovarian cancer, not only serous papillary type (PR), but also in endometrioid and transitional cell tumors (SD > 6 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notch is a key pathway in ovarian cancer, and Dll4 is overexpressed in up to 72% of ovarian carcinomas (15,29). Enoticumab had activity in patients with ovarian cancer, not only serous papillary type (PR), but also in endometrioid and transitional cell tumors (SD > 6 months).…”
Section: Discussionmentioning
confidence: 99%
“…Increased Dll4 expression has been noted in several tumor types (4,(13)(14)(15), and it may be associated with worse outcomes (13,(15)(16)(17). Preclinically, Dll4 blockade has activity against tumor xenografts such as colorectal, sarcoma, lung, breast, pancreas cancers, melanoma, and glioma, and includes tumors resistant to anti-VEGF agents (7,11,18).…”
Section: Introductionmentioning
confidence: 99%
“…In human tumors, Dll4 expression is typically restricted to the tumor vasculature, and low to undetectable in the vasculature of adjacent normal tissue (13,(18)(19)(20)(21)(22). In breast and ovarian cancer, Dll4 expression appears correlated to clinical outcome (18,23).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have shown that silencing of EZH2 using siRNA inhibits angiogenesis and ovarian cancer growth (15). Dll4 has been associated with poor outcome following anti-VEGF therapy and RNA interferencemediated silencing of Dll4 has been shown to reduce angiogenesis and tumor growth in ovarian cancer models (16). This approach appears promising and a phase I clinical trial of REGN 421, a monoclonal antibody against Dll4, is underway.…”
Section: Angiogenesis Inhibitorsmentioning
confidence: 99%